Redistribution through public choice - Hochman, Harold M.; Peterson, George E.; National Science Foundation (U.S.).; Urban Institute (New York ; London : Columbia University Press, 1974)
This book focuses on the emergence of distribution and redistribution.
Published in cooperation with the Urban Institute, Washington, D.C.
Revised versions of papers presented at a conference sponsored by the National Science Foundation and the Urban Institute, held Mar. 23-24, 1972.
Includes bibliographical references.
osa 14/07/17
Loans
Keywords: Income